CSPα, a Molecular Co-chaperone Essential for Short and Long-Term Synaptic Maintenance - Lopez-Ortega, Elena; Ruiz, Rocío; Tabares, Lucia (Frontiers in Neuroscience, 2017)
Cysteine string protein α (CSPα) is a vesicle protein located in the presynaptic terminal of most synapses. CSPα is an essential molecular co-chaperone that facilitates the correct folding of proteins and the assembly of the exocytic machinery. The absence of this protein leads to altered neurotransmitter release and neurodegeneration in multiple model systems, from flies to mice. In humans, CSPα mutations are associated with the development of neuronal ceroid lipofuscinosis, a neurodegenerative disease characterized by intracellular accumulation of lysosomal material. Here, we review the physiological role of CSPα and the pathology resulting from the homozygous deletion of the gene or its mutations. In addition, we investigate whether long-term moderate reduction of the protein produces motor dysfunction. We found that one-year-old CSPα heterozygous mice display a reduced ability to sustain motor unit recruitment during repetitive stimulation, which indicates that physiological levels of CSPα are required for normal neuromuscular responses in mice and, likely, in humans.